Analisis Preferensi Konsumen terhadap Sepatu Ramah Lingkungan: Studi Kasus di Kota Semarang - Alam, Sairul; Ulkhaq, Mujiya; Handayani, Naniek Utami (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This study aims to analyze consumer preferences toward eco-friendly shoes by identifying the most influential attributes affecting purchasing decisions, including price, recycled materials, durability, ecolabel, and recyclability. Design/Methode/Approach: A quantitative approach was employed using Choice-Based Conjoint Analysis (CBCA) to evaluate consumer preferences for sustainable footwear. Research Finding: Price emerged as the most influential attribute, with consumers preferring products priced between IDR 500,000–1,000,000. Recycled materials and product durability had significant positive utilities, indicating strong consumer preference for environmentally sustainable shoes. Ecolabels also played a key role, showing that certified products are more appealing. However, training shoes were less preferred compared to casual and running shoes. Theoretical contribution/Originality: This study contributes to sustainable fashion literature by empirically highlighting the relative importance of sustainability-related attributes in consumer purchasing behavior within the footwear industry. Practitioner/Policy implication: Manufacturers and marketers should emphasize affordable pricing, use of recycled materials, durability, and ecolabel visibility to align with consumer preferences and strengthen environmental positioning. Research limitation: This study focuses on Indonesian consumers; future research should include broader samples to enhance generalizability.